Human-computer interaction fundamentals and practice - Kim, Gerard Jounghyun (CRC Press, Taylor & Francis Group, 2015)
This book goes through the whole cycle of HCI design and implementation and explains the core and basic HCI concepts behind each step. The book uses an interface for an actual Android app, designed and evaluated from the ground up, as a concrete example. Understandable to those with minimal programming knowledge, the book provides readers with a basic working knowledge of HCI oriented software development.